Chaos in nursing: make it work for you. - Vicenzi, A E; White, K R; Begun, J W (The American journal of nursing, 1997)
Place: United States Vicenzi, A E. Department of Nursing, Southern Connecticut State University, New Haven, USA.
Keywords: *Health Facility Environment; *Nurses/px [Psychology]; *Nursing; Adaptation; Psychological; Humans; Interprofessional Relations; Organizational Innovation; dept.nur; ❓ Multiple DOI

The application of nonlinear dynamics in nursing research - Hamilton, Patti; Pollock, Jane Englebright; Mitchell, null De Ann F.; Vicenzi, Angela E.; West, Bruce J. (Nonlinear Dynamics, Psychology, and Life Sciences, 1997)
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00201 tex.type: [object Object]
Keywords: dept.nur

Differences in Classroom Teaching Preferences between Traditional and Adult BSN Students - Thompson, C.; Sheckley, B.G. (Journal of Nursing Education, 1997)
The primary purposes of this study were to identify the best teaching practices for adult baccalaureate (BSN) nursing students and to examine if adult students' teaching preferences differed from those of traditional BSN students. The sample consisted of 206 adult and traditional students in four BSN programs. The adult nursing student sample was further subdivided into two groups: adults with no prior nursing education (adult non-nurses) and adults with prior nursing education (RN'S). Using a two-part, self-administered questionnaire, respondents were asked to rate the frequency with which 41 teaching strategies were used in their best and in their worst classroom learning experiences in nursing. In most cases, adult non-nurses' teaching preferences did not vary significantly from the preferences of traditional students. However, adults with no prior nursing education did show a preference for knowledgeable and organized instructors. In contrast RNs' preferred classroom situations were where time on task was emphasized, cooperative learning was encouraged, and expectations for learning were high. Results indicate that classroom teaching preferences vary as a function of prior experience with the subject matter and are not attributable to age itself. Findings suggest that prior experience with course content is a more important consideration in planning programs than generalized adult experience.
26 citations (Crossref) [2023-10-31]
Keywords: *Choice Behavior; *Education; Nursing; Associate; *Education; Nursing; Baccalaureate; *Education; Professional; Retraining; *Students; Nursing/px [Psychology]; *Teaching/st [Standards]; Adolescent; Adult; Choice Behavior; Education; Nursing; Associate; Education; Nursing; Baccalaureate; Education; Professional; Retraining; Factor Analysis; Statistical; Humans; Middle Aged; Nursing Education Research; Questionnaires; Students; Nursing; Surveys and Questionnaires; Teaching; adolescent; adult; article; comparative study; continuing education; decision making; dept.nur; factorial analysis; human; middle aged; nursing education; nursing student; psychological aspect; questionnaire; standard; teaching